2014
DOI: 10.1109/tvcg.2014.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Virtual Human Animation on Emotion Contagion in Simulated Inter-Personal Experiences

Abstract: We empirically examined the impact of virtual human animation on the emotional responses of participants in a medical virtual reality system for education in the signs and symptoms of patient deterioration. Participants were presented with one of two virtual human conditions in a between-subjects experiment, static (non-animated) and dynamic (animated). Our objective measures included the use of psycho-physical Electro Dermal Activity (EDA) sensors, and subjective measures inspired by social psychology researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…One powerful tool to enhance experimental control over such dynamic social interactions has been the use of avatars or virtual reality (Wu et al, 2014), and also the use of picture morphing interfaces (Fukuta et al, 2014). For example, a recent study shows that the use of virtual reality tools may present a number of advantages when dealing with patients suffering from schizophrenia, such as symptom assessment, identification of symptom markers, or the investigation of the differential prediction of symptoms (Freeman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…One powerful tool to enhance experimental control over such dynamic social interactions has been the use of avatars or virtual reality (Wu et al, 2014), and also the use of picture morphing interfaces (Fukuta et al, 2014). For example, a recent study shows that the use of virtual reality tools may present a number of advantages when dealing with patients suffering from schizophrenia, such as symptom assessment, identification of symptom markers, or the investigation of the differential prediction of symptoms (Freeman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, emotional contagion refers to emotional contagion susceptibility. Studies have found that emotional contagion played a substantial role in affecting receivers’ mood states among infants (Waters et al, 2017), adolescent siblings (Serra Poirier et al, 2017), and adults (Wu et al, 2014; Volante et al, 2016). More often, emotional contagion has been found to play a key role in industrial and organizational areas among adults.…”
Section: Introductionmentioning
confidence: 99%
“…First, we examined the relation between emotional contagion and mood state among children. A typical limitation of previous studies has been that most of the research about emotional contagion has focused on adults (e.g., Kramer et al, 2014; Wu et al, 2014; Fan et al, 2016; Volante et al, 2016). According to computer searches of PsycInfo, 417 of 690 studies focused on adults, 53 studies focused on adolescents, and 54 studies focused on children.…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy persisted despite providing additional text or audio context through scripted conversations. It is possible that the intensity of the “sad” emotion animation was not adequate or that it may have been perceived by participants as a blend of emotions when only one forced choice response was available [ 13 ]. Previous studies noted similar accuracy levels for happiness , afraid , sadness , and angry using photographic images of facial expressions of emotion [ 14 ].…”
Section: Discussionmentioning
confidence: 99%